New Museology Approaches in Cultural Heritage Centers - Yum, Mehmet Sinan (Journal of Interior Design and Academy, 2024)
Museums and historical buildings are currently being evaluated for different functions to transfer the social heritage created by the social and cultural values they carry to new generations such as Tofaş Anatolian Cars Museum and Umurbey Bath in Bursa. The museum dedicated to the narration of cultural heritage, presents toy car collections and other periodic toys to visitors in the Carousel exhibition within the historical bath structure as an exhibition space in the new museology concept. The research presents the processes and results of an edutainment project in line with the objectives by examining the exhibition organized by Mido Architecture, Trio Design, and the design studio partnered by the author. To put forth the validity of the study, the research emphasizes the edutainment design process of an architectural user experience concept from an interdisciplinary perspective centered on cultural heritage.